Building the Social Cascade: Connecting Culture, Disaster, and Persecution in the 1730s - Sundberg, Adam (Journal for the History of Environment and Society, 2023)
Abstract This article presents a framework to map connectivity between seemingly independent crises, using as an example a moral panic and a “natural disaster” in the 1730s. The first was a wave of sodomy trials and executions in the Dutch Republic. The second was the infamous shipworm epidemic, which catalysed a water management crisis and short-lived existential panic. This paper argues that the sodomy persecution and the shipworm disaster were integral components of a “social cascade”. Rather than background conditions, social-ecological and cultural conditions in the Dutch Republic established pathways and set the bounds for causal connections that knit social, environmental, and cultural crises together. The cultural perception of crises, and its interaction with an evolving metanarrative of decline, supplied the causal link. The social cascade framework enriches our understanding of crisis connectivity and encourages new interpretations of the relationships between disaster, environmental change, and culture.
Keywords: eighteenth century